Bird's-eye view looking east from center of Nome showing the waterfront, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Looking East from centrr of Nome, Alaska" Original image in Hegg Album 38, page 14. Original photograph by Eric A. Hegg 1340; copied by Webster and Stevens 271.A.